Semi-quantitative analysis of morphological changes in bee tissues: A toxicological approach - Grella, Tatiane Caroline [UNESP]; Soares-Lima, Hellen Maria; Malaspina, Osmar [UNESP]; Ferreira Nocelli, Roberta Cornelio (Elsevier B.V., 2019)
During foraging, bees are exposed to sublethal doses of insecticides, which can cause morphological changes to various organs, such as the midgut, Malpighian tubules, and mushroon body. Thus, the purpose of this study was to establish a scoring system to evaluate these alterations based on the damage caused and its reversibility. Therefore, a grade 1 score indicates a minimal and easily reversible lesion, increased apocrine secretion, increased cell elimination into the lumen, and a larger quantity of spherocrystals; grade 2 was assigned to moderate and typically reversible injuries, such as changes in the brush border, vacuolation/loss of cytoplasmic material, presence/height of the brush border, and cell swelling; and grade 3 was assigned to serious and irreversible, loss of cell nests of regenerative cells, pyknosis, and loss of contact between Kenyon cells. In addition, frequency values were assigned since the alterations can occur at different frequencies according to the insecticide and the bees exposed; the frequency ranges from 0 to 6, with 0 representing the absence of an alteration and 6 representing a high frequency occurrence. Based on the analyses, we conclude that each change causes morphological damage, which may or may not be irreversible and could affect the health of the colony. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Midgut; Malpighian tubules; Mushroom body; Score; Insecticide